Lived experience in patients with recurrent glioblastoma in Japan: A narrative study - Ai Chikada; Asako Takekuma Katsumata; Mariko Asase; Sayaka Takenouchi; Yoshiki Arakawa; Kazuko Nin (JMIR Publications, 2017)
Glioblastoma (GBM) is well known to have one of the poorest prognoses among all cancers. Patients with GBM in progression-free survival (PFS) may be relatively stable and can often maintain their quality of life. Thus, PFS is a desirable goal. In Japan, the median PFS is 11 months. It is difficult to grasp a patient's thoughts and hopes when, after PFS, they are readmitted due to recurrence or acute deterioration. Therefore, this study aimed to de-scribe the lived experience of illness in patients with recurrent GBM, focusing on PFS. We enrolled five patients into the study; however, only four patients completed data collection. Data were collected using semi-structured inter-views. We also conducted a thematic narrative analysis. As a result, we generated one overall theme: Even in vul-nerable and constrained daily lives, the aim was gaining a sense of stability-and maintaining it steadily-as far as possible, on their own. That sense of stability is fragile so that maintaining equilibrium is a precarious enterprise. Moreover, in PFS, participants were trying to maintain equilibrium by reevaluating themselves and sometimes giving up something, although they received support from people around them. We infer that it is important for nurses to assess and understand the fluctuations in that sense of stability through continuous involvement with patients. An interdisciplinary approach and lateral integration of care are important to meet the needs of GBM patients. This understanding will lead to nursing supports that help patients live with stability, pride, and dignity.